2005
DOI: 10.1111/j.1365-3083.2005.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Induces IL‐10‐Producing Monocyte‐Derived Dendritic Cells with Durable Immaturity

Abstract: It is highly desirable that immature dendritic cells (DC) used for tolerance induction maintain steady immature state with predominant interleukin (IL)-10 production. In this study, we attempted to develop DC with durable immaturity and other tolerogenic features by using dexamethasone (Dex). We found DC derived from human monocytes in the presence of 10 À7 M Dex were negative for CD1a. Compared with control transduced DC (Ctrl-DC), Dex-DC expressed lower CD40, CD80 and CD86 but equivalent human leucocyte anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
79
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 57 publications
15
79
1
8
Order By: Relevance
“…Similar observations have been made with human moDC treated with Dex [10,17]. In addition, Dex-DC possess durable immaturity [10] as high IL-10 and little IL-12 production was maintained up to 5 days after removal of Dex. In vivo, application of Dex-DC prior to allograft transplantation significantly prolonged the survival of the grafts in an antigendependent fashion in mice [16,18].…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Similar observations have been made with human moDC treated with Dex [10,17]. In addition, Dex-DC possess durable immaturity [10] as high IL-10 and little IL-12 production was maintained up to 5 days after removal of Dex. In vivo, application of Dex-DC prior to allograft transplantation significantly prolonged the survival of the grafts in an antigendependent fashion in mice [16,18].…”
supporting
confidence: 69%
“…For example, DC treated with either dexamethasone (Dex) or the active form of vitamin D, 1a,25-dihydroxyvitamin D 3 (VD3), arrest DC in a semimature state and prevent the up-regulation of co-stimulatory Treatment of murine immature bone marrow-derived DC with Dex prior to LPS-induced activation results in modulated DC that inhibit the proliferation of allo-specific T cells in both primary and secondary MLR [8,16]. Similar observations have been made with human moDC treated with Dex [10,17]. In addition, Dex-DC possess durable immaturity [10] as high IL-10 and little IL-12 production was maintained up to 5 days after removal of Dex.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…PC12 cells, melanocytes, gastric and intestinal epithelial cells, elevation of cAMP results in ERK1/2-activation via a B-RAF -MEK1/2 pathway [12,40,51], which may also be responsible for Ctx-induced ERK activation in porcine MoDC. Functionally, ERK1/2 activation has been associated with high levels of IL-10 secretion by DC [52], which is consistent with our findings. It has been previously demonstrated that functional DC maturation involves NFκB activation [39].…”
Section: Discussionsupporting
confidence: 92%
“…В настоящее время активно исследуется влияние различных иммуносупрессивных лекарств на дифференцировку ДК и их функцию [118]. Среди наиболее часто используемых лекарств для генерации толерогенных ДК в лабораторных условиях -дексаметазон, уже упоминавшийся витамин D 3 (1a,25(ОН) 2 D 3 и его аналоги), а также рапамицин [64,65,[119][120][121][122][123][124][125]. Все эти лекарства имеют общее свойство -они индуцируют дифференцировку фенотипически зрелых ДК, которые имеют низкую стимулирующую способность Т-клеток и не становятся иммуностимуляторами в ответ на сигналы зрелости ДК.…”
Section: дендритные клетки (дк) (Dc)unclassified